Effect of cerium doping on the structure, magnetic, electric and dielectric properties of spinel nano-magnets Mn0.5Zn0.5Fe2O4 - Ullah, Ihsan; Khan, Qaisar; Ahmad, Rashid; Ahamd, Iftikhar; Khan, Imad (Applied physics. A, Materials science & processing, 2024)
Cerium doped Mn 0.5 Zn 0.5 Fe 2 O 4 spinel nano-magnets were synthesized using sol–gel technique and characterized through x-ray diffraction (XRD), Fourier transform-infrared radiation (FT-IR), impedance analyzer, modulus spectroscopy, scanning electron microscopy (SEM), vibrating sample magnetometer (VSM) and energy dispersive x-ray spectroscopy (EDX). The cations redistribution with Ce 3+ substitution strongly affect the physical properties of the samples. Single phase spinel structure is identified for the synthesized samples and the crystal imperfection is found low. The lattice parameters reduce with Ce 3+ concentration due to lanthanide contraction. The saturation magnetization of Mn 0.5 Zn 0.5 Ce x Fe 2− x O 4 is found maximum for the x = 0 sample. The measured magnetic properties such as coercivity (H c ), retentivity (M r ) and saturation magnetization (M s ) decrease with increase in Ce 3+ concentration. The synthesized samples show positive values of magnetic susceptibility which show anti-ferromagnetic/ferrimagnetic nature. The SEM images show increase in size of the grain with increasing sintering conditions parallel by significant decrease of pores, the position and the existence of tetrahedral and octahedral sites. The FT-IR spectra reveal the metal–oxygen oscillations at tetrahedral and octahedral sites. The dielectric constants are found in the range −118.6 to −242.5 at 2 MHz, which revealed moderate strain sensitivity, low ac conductivity and low dielectric loss. At low frequency range the synthesized samples are promising materials for stress sensor applications.